Characterization and Risk Assessment of Heavy Metals in Surface Sediments From Jian and Moyang Rivers in Western Guangdong - Feng, Jie; Lin, Yuemin; Li, Mingkun; Ouyang, Tingping; Yu, Mingjie (Frontiers in Environmental Science, 2022)
The river environment is complex and receives a variety contaminants from numerous sources that are persistent, bioaccumulative and toxic. The distribution, source, contamination and ecological risk status of Zn, Pb, Cu, Ni, Cr and Cd were evaluated in the surface sediments at 45 sites on the Moyang and Jian Rivers in Western Guangdong, China. Single pollution indices, including contamination factor (CF) and enrichment factor (EF), revealed that Zn, Pb, Ni, Cu and Cd showed moderate to significant enrichment. To overcome the limitation of the single element indices, a range of sediment quality indices, including modified contamination index (mCd), pollution index(PI) and modified pollution index(MPI) were utilised to ascertain the sediment quality. The sediment in the study area is deemed to be slightly to extremely polluted. The sediment quality guidelines (SQGs), potential ecological risk index (RI) and modified ecological risk index (MRI) were used to assess possible ecological risks. According to the SQGs, Pb, Ni and Cu have the potential to induce biological effects. The RI indicated that the sediment poses a low ecological risk. However, the MRI indicated that the ecological risk of the sediment was moderate to very high. The accuracy of the single and multi-element indices and ecological risk assessment were evaluated in the river using, the principal component analysis (PCA) and cluster analysis (CA), showing an anthropogenic impact. Results demonstrate the need to pay attention to the ecological environment of small rivers, which is are sensitive to their surroundings.